Deteksi Immunoglobulin M dengan antigen Outer Membrane Protein (OMP) 50K-DA salmonella typhi pada demam tifoid - Herawina E; Zulfikar Lubis; Ricke Loesnihari (Fakultas Kedokteran USU, 2016)
Introduction : Typhoid fever is a systemic infectious disease caused by Salmonella typhi. That is still widely found in the world and many developing countries that are mainly located in the tropical and subtropical. Clinical diagnosis of typhoid fever is difficult because there is no typical clinical manifestation, therefore we need laboratory tests. Typhidot IgM is one of serological examination is a rapid examination with of detecting the presence of antibodies IgM of Outer membrane protein (OMP) 50KDa antigen in Salmonella typhi.The aim of this study was to assess the sensitivity and specificity of the IgM antigen examination of Outer membrane protein (OMP) 50KDa Salmonella typhi with blood culture.Methods : The method that was used in this study was diagnostic testing to compare rapid examination Typhidot IgM with blood cultures in adult patients ≥ 18 years old, with fever≥38º, fever ≥3 days, who were diagnosed with suspected typhoid fever or typhoid fever based on Nelwan score in Haji Adam Malik Hospital.Results : The number of subjects are 29 people, with 25 positive Typhidot IgM (86%) and 11 positive blood cultures (38%). The examination results of Typhidot IgM towards blood culture showed 100% sensitivity, 22% specificity, 45% positive predictive value and 100% negative predictive value.Conclusion : The results of rapid examination Typhidot IgM showed a good sensitivity and a poor specificity, with a negative predictive value of 100% which indicates that rapid examination Typhidot IgM can not be use a diagnostic examination but Typhidot IgM can be use as an initial screening examination this means that Typhidot IgM able to get rid of a case that really is not typoid fever.Keyword : Typhoid fever, rapid test Typhidot , Blood Cultures.